Tasawuf antara Kesalehan Individu dan Dimensi Sosial - Ahmad Nurcholis (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
Within this modern era, where Islamic doctrines have been more eroded by the advance of scientific development, the power of umma has gradually decreased as a result of the abandonment of the spirit of jihâd al-nafs. There would be no other way except to revive Islamic Sufism's principles and values without leaving the rational way of thinking and escaping from social realities. When humans recognize their God, it would be easier for them to perform everything God commands them. Where did humans come from and where they will go to are among philosophical questions that the Sufi. These are foundations for the Sufis to “recognize their selves”, since by recognizing the self, God can be, then, recognized. Tasawuf is a way, which leads to qalb salîm (a pure heart). Many classic books discuss this, and the discussion deals with: firstly, efforts to straighten deeds, khushû‘, and courtesy of worship; secondly, ways of mujâhadah, self and heart purification, and abolishing madhmûmah (bad manners) and replacing them with mahmûdah (commendable conducts); thirdly, ma‘rifat, rabbânîyah, wahbîyah knowledge, dhawq, wijdânîyah, and nature of kashf.